Faktor Yang Mempengaruhi Nasabah Non Muslim dalam Bertransaksi di Perbankan Syariah - Anggraini, Yulia; Umah, Restu Yulia Hidayatul (Proceedings of Annual Conference for Muslim Scholars, 2022)
Abstract: This study aims to describe in more depth what factors influence non-Muslim customers who carry out financial transactions, both funding, and lending in Islamic banking. The research subjects are non-Muslim customers who carry out financial transactions, both funding, and lending at Bank Syariah Indonesia Nganjuk Branch Office. Philip Kottler and Armstrong state that there are five indicators that influence the decision to transact in Islamic banking, namely problem recognition, information seeking, evaluation of alternatives, buying decisions, and post-purchase behavior. Religion is the relationship between creatures and their God, which is manifested in their inner attitude and is seen in the worship they do, and is also reflected in their daily attitudes, including in choosing decisions to make financial transactions in banking that are not in accordance with their religion. The approach in this study is a qualitative approach using field research, with data collection techniques using interviews. From the results of the analysis, it is found that non-Muslim customers who make transactions in Islamic banking have used all indicators in deciding which Islamic banking to use, where profit-sharing factors both in funding and lending play the most important role, so they choose banks that are not in accordance with religion. which he adheres to.